CARBON CYCLES, NITROGEN FIXATION AND THE LEGUME-RHIZOBIA SYMBIOSIS AS SOIL CONTAMINANT BIOTEST SYSTEM - Werner, Dietrich (Secretariat of Forestry Research and Development Agency, 2008)
The major pools and turnover rates of the global carbon (C) cycles are presented and compared to the human production of CO2 from the burning of fossil fuels (e.g. coal and oil) and geothermal fuels (natural gases), both categorized as non-renewable energy resources which in amount reaches around 6.5 Gigatons C per year. These pools that serve as C-holding stallions are in the atmosphere, the land plant biomass, the organic soils carbon, the ocean carbon and the lithosphere. In another related case, the present focus in the area of nitrogen fixation is discussed with data on world production of grain legumes compared to cereals production and nitrogen fertilizer use. The focus to understand the molecular biology of the legume-rhizobia symbiosis as a major contributor to nitrogen fixation is in the areas of signal exchange between host plants and rhizobia in the rhizophere including the nod factor signalling, the infection and nodule compartmentation and the soils stress factors affecting the symbiosis. The use of the Legume-Rhizobia symbiosis as a biotest system for soil contaminants includes data for cadmium, arsenate, atrazine, lindane, fluoranthene, phenantrene and acenaphthene and also results on the mechanism, why the symbiotic system is more sensitive than test systems with plant growth parameters.